Cloning, Expression and Characterization of Membrane Bound FtsH Protease of Geobacillus kaustophilus - Tulek, A.; Ozdemir, F., I; Ramadhan, S. S. (Pleiades Publishing Inc, 2020)
FtsH is a unique enzyme as a membrane-bound ATP-dependent zinc-metalloprotease that degrades integral membrane proteins as well as cytoplasmic proteins. It spans the cell membrane twice and has a large cytoplasmic C-terminal with protease and ATP-binding domain. The ATPase and proteolytic activity of soluble FtsH protease from thermophilic Geobacillus kaustophilus strain DSM 7263T which lacked the transmembrane helices was studied. The 1530 bp gene was cloned in pET14b vector and expressed in Escherichia coli BL21(DE3) cells. The recombinant protein containing 6xHis-Tag at N-terminus was purified and enzyme characterization was performed. The molecular mass of N-terminal truncated FtsH was determined as similar to 58 kDa from SDS-PAGE and Western blotting analysis. The optimum ATPase activity was observed at 55 degrees C. In addition to ATP, the enzyme is also capable of hydrolyzing CTP and at a lesser extent GTP. The ATPase activity of FtsH was inhibited by 10 mM EDTA and O-phenanthroline, at 65 and 48%, respectively and almost completely inhibited in the presence of 1 mM lactacystin or PMSF. Purified FtsH degraded alpha-casein efficiently (up to 96-98%) in the presence of 4 mM ATP. Our results showed that without N-terminal transmembrane domain FtsH showed an efficient ATPase and protease activity.
Keywords: ATP-dependent protease; FtsH protease; membrane-bound protease; thermophilic; Geobacillus kaustophilus